Phrenology and the average person, 1840–1940. (April 2021) - Sysling, Fenneke
The popular science of phrenology is known for its preoccupation with geniuses and criminals, but this article shows that phrenologists also introduced ideas about the 'average' person. Popular phrenologists in the US and the UK examined the heads of their clients to give an indication of their character. Based on the publications of phrenologists and on a large collection of standardized charts with clients' scores, this article analyses their definition of what they considered to be the 'average'. It can be concluded that phrenologists were some of the first to teach individuals to see their identity in relation to an imagined statistical community.